2005
DOI: 10.1111/j.1365-2621.2005.00995.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of flour fortification with haem liposome on bread and bread doughs

Abstract: Slaughter blood haem was encapsulated in lecithin : cholesterol Liposomes. Wheat flour was fortified with this mixture at two levels (60 and 100 mg/100 g flour) using the haem liposomes as iron source. The effect of haem fortification on gluten and fat content of flours was determined, as were the effects of fortification on dough visco-elastic characteristics (water absorption, development time, dough stability and breakdown time). The baking properties of the breads were also investigated. The addition of ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…They are known for their high encapsulation efficiency, simple production method, and high physical stability in products with high water activity [4]. They have been successfully used for encapsulation of various food ingredients such as enzymes [5], vitamins [6], food preservatives [7], and various sources of soluble iron [8][9][10][11], although some negative side effects have also been reported with regard to oxidation of the building blocks of the liposomes, i.e., unsaturated phospholipids [12].…”
Section: Introductionmentioning
confidence: 99%
“…They are known for their high encapsulation efficiency, simple production method, and high physical stability in products with high water activity [4]. They have been successfully used for encapsulation of various food ingredients such as enzymes [5], vitamins [6], food preservatives [7], and various sources of soluble iron [8][9][10][11], although some negative side effects have also been reported with regard to oxidation of the building blocks of the liposomes, i.e., unsaturated phospholipids [12].…”
Section: Introductionmentioning
confidence: 99%
“…Among the different iron compounds that can be used, heme iron has a particularly high bioavailability, which is higher than that of inorganic iron mainly because the inhibition of heme iron absorption by food ligands is low [2], and also their absorption process is different [3]. As a result, trials have taken place to fortify different foods such as biscuits [4,5], cookie fillings [6], weaning foods [7], flour [8], and black beans [9] with heme iron.…”
mentioning
confidence: 99%
“…They are known for their high encapsulation efficiency, simple production method, and high physical stability in products with high water activity (Desai & Park, 2005). They have been successfully used for encapsulation of numerous food ingredients such as enzymes (Kheadr et al, 2002), vitamins (Tesoriere et al, 1996), food preservatives (Malheiros et al, 2010) and various sources of soluble iron (Albaldawi et al, 2005;Ding et al, 2009;Kosaraju et al, 2008;Xia & Xu, 2005), although also some negative side effects have been reported with regard to oxidation of the building blocks of the liposomes, i.e., unsaturated phospholipids .…”
Section: Introductionmentioning
confidence: 99%